Teaching Philosophy Statement: It is time to think outside the box - Sharmin, Nazlee; Chow, Ava K. (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2023)
The teaching philosophy statement in Canadian academia is integral to applying for faculty positions, promotions, awards, and grants. However, the notion of philosophy is quite unfamiliar to many science students and educators, which is one main audience for this Note from the Field. Moreover, teaching is no longer limited to a traditional didactic model. During the COVID-19 pandemic, many new technology-infused, online, and hybrid teaching models became popular. Years-old philosophies no longer fit with many of the latest innovative teaching approaches. We suggest considering some creative but equally effective alternatives for formal teaching philosophy statements. A reflective essay or short video introduction are two such possibilities which can be equally effective in evaluating one’s teaching practices and goals.